Objective, observer-independent evaluation of myocardial perfusion and function: the role of SPECT - Szot, Wojciech; Kwiecień, Ewa; Tekieli, Łukasz; Czyż, Łukasz; Borkowska, Eliza; Dąbrowski, Władysław; Drabik, Leszek; Dąbrowski, Maciej; Kostkiewicz, Magdalena; Musiałek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2022)
The number of patients with coronary artery disease and ischaemic heart failure – and those with terminal heart failure – is increasing despite improvements in medical and interventional therapies of ischaemic heart disease – and, over the next decades, it is projected to continue to increase further. Observer-independent, reproducible imaging techniques play a fundamental role in objective evaluation of both conventional (such as surgical or percutaneous) myocardial revascularization and novel therapeutic approaches to reduce myocardial ischaemia, improve contractility and prevent adverse myocardial remodelling. To be applicable to clinical practice, the clinical study design and data should best be rooted in everyday clinical practice. Accurate and reproducible assessment of left ventricular ejection fraction, left ventricular volumes, myocardial perfusion and function is one of the most important objectives of cardiac imaging. Current techniques used both in clinical studies and in everyday clinical practice include 2- and 3-dimensional echocardiography, magnetic resonance imaging, single-photon emission computed tomography and positron emission tomography; each of these has its strengths and limitations. We review present evidence on the role of single-photon emission computed tomography as a technique that may offer, through being observer-independent, the most objective evaluation of evolution of left ventricular perfusion, volumes and ejection fraction.